2020
DOI: 10.1108/mhrj-12-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Online mental health communities, self-efficacy and transition to further support

Abstract: Purpose This study is exploratory research which aims to understand how users gain support from the online mental health community (OMHC) 18 percent and whether engagement with this community may possibly lead to increased self-efficacy. Design/methodology/approach In total, 128 users of an OMHC, 18 percent, completed an online questionnaire that asked open-ended questions about the community and how users engaged with it. The results were analysed using quantitative and qualitative methods. Findings Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The fact that people are not able to speak about their emotions and feelings in fear of being stigmatized may reduce psychological well-being indeed, and open online forums can serve as support platforms that enabled people to share and discuss their experiences without face-to-face pressure. These results are in line with previous studies that have found mental health forum participation useful for social support – it may be easier to discuss personal problems online than face-to-face (e.g., Prescott et al, 2020 ). A large part of these discussions took place in general question forums, which indicates that fictophilia, as a recently popularized phenomenon, provokes confusion to an extent that people seek advice for understanding and dealing with related experiences.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that people are not able to speak about their emotions and feelings in fear of being stigmatized may reduce psychological well-being indeed, and open online forums can serve as support platforms that enabled people to share and discuss their experiences without face-to-face pressure. These results are in line with previous studies that have found mental health forum participation useful for social support – it may be easier to discuss personal problems online than face-to-face (e.g., Prescott et al, 2020 ). A large part of these discussions took place in general question forums, which indicates that fictophilia, as a recently popularized phenomenon, provokes confusion to an extent that people seek advice for understanding and dealing with related experiences.…”
Section: Discussionsupporting
confidence: 92%
“…The forums offer peer support, a type of service which has proven effective in supporting mental wellness, both face-to-face and online [ 2 , 20 , 21 , 22 ]. Institutional trust and reputation foster a large network of users and a bank of past experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Most, including the forums in this research, are facilitated by nonprofit mental health organisations. Such models of online peer support have been found to deliver considerable mental health benefits [ 20 ] through providing emotional and informational support [ 21 ], social connectedness, empowerment and helping people cope [ 2 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Online mental health forums are specifically focused on mental health issues and are spaces where individuals can freely discuss their mental health issues ( 9 ). Such forums are available 24/7 meaning that support can be accessed when it is needed most ( 11 ). Both general health and mental health forums are typically constructed around peers providing support and advice to each other ( 12 ), however some forums are also overseen by moderators ( 13 ).…”
Section: Introductionmentioning
confidence: 99%